2006
DOI: 10.1007/s11274-006-9203-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and PCR detection of Enterobacter sakazakii in South African food products, specifically infant formula milks

Abstract: Enterobacter sakazakii has recently been identified as an opportunistic pathogen. The current culture-dependent detection methods for these bacteria are time-consuming and in this study a PCR method for the detection of E. sakazakii in South African food products, including an internal amplification control (IAC) was developed. DNA was isolated and amplified from the products and they were plated on selective growth media after pre-enrichment and enrichment in Enterobacteriaceae enrichment broth. Four of the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
2
4
0
1
Order By: Relevance
“…Based on sequencing results, all 12 isolates selected from 9 of 72 PIF samples (12.5%) investigated in this study were identified as Cronobacter (Figure 1). The incidence of 12.5% Cronobacter contamination of PIF in Malaysia was almost in agreement with reports of Cawthorn et al (2008) and Witthuhn et al (2006) who found the prevalence of Cronobacter in South African PIF were 14 and 18%, respectively. Muytjens et al (1988) also reported that 14% of PIF samples were positive for Cronobacter contamination.…”
Section: Resultssupporting
confidence: 90%
“…Based on sequencing results, all 12 isolates selected from 9 of 72 PIF samples (12.5%) investigated in this study were identified as Cronobacter (Figure 1). The incidence of 12.5% Cronobacter contamination of PIF in Malaysia was almost in agreement with reports of Cawthorn et al (2008) and Witthuhn et al (2006) who found the prevalence of Cronobacter in South African PIF were 14 and 18%, respectively. Muytjens et al (1988) also reported that 14% of PIF samples were positive for Cronobacter contamination.…”
Section: Resultssupporting
confidence: 90%
“…Until recently, real-time PCR approaches have been widely used in detection of Cronobacter spp. strains (Liu et al 2006;Witthuhn et al 2007). Although real-time PCR assay had many advantages over conventional PCR that include higher sensitivity and easy standardization, it nevertheless has many disadvantages as well.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that powdered milk-based infant formulas may serve as a transmission route. Thus, detection of the pathogen has been an important subject in clinical research and food safety (ICMSF 2002;Liu et al 2006;Witthuhn et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…All of these products, however, met the prevailing Codex Alimentarius Commission (CAC) microbiological specifications for coliform counts in powdered IFM (less than 3 cfu g À1 ) (Muytjens et al, 1988;Van Acker et al, 2001). Evaluation of commercial powdered IFM and baby foods available on the South African market revealed the presence of Cronobacter in 18% of the products tested (Witthuhn, Kemp, & Britz, 2006).…”
Section: Presence Of Cronobacter In Infant Formula Milkmentioning
confidence: 99%